2010
DOI: 10.1097/yct.0b013e3181c185f9
|View full text |Cite
|
Sign up to set email alerts
|

One Hundred Twenty Years of Mental Health Care in Thailand and the Development of Electroconvulsive Therapy

Abstract: Through cooperation with all available public and private agencies and through the support given to encourage active participation in the community, mental health care in Thailand continues to improve and evolve. However, regarding ECT development, little has been done despite a high ECT use rate, and as such, some form of reform is needed to achieve and maintain optimal standards in its practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 1 publication
(3 reference statements)
1
9
0
Order By: Relevance
“…40 This rate of ECT use is higher than that in Thailand (0.01 patient treated per 100) 41 and Hungary (0.6 per 100). One study in Hong Kong found that the rate of ECT use ranged from 1.34 to 1.88 patients treated per 100 inpatients discharged.…”
Section: Indications and Patterns Of Usementioning
confidence: 79%
“…40 This rate of ECT use is higher than that in Thailand (0.01 patient treated per 100) 41 and Hungary (0.6 per 100). One study in Hong Kong found that the rate of ECT use ranged from 1.34 to 1.88 patients treated per 100 inpatients discharged.…”
Section: Indications and Patterns Of Usementioning
confidence: 79%
“…Explanations of these variations are complex, encompassing not only the diversity in organization of psychiatric services, but no doubt also grounded in professional beliefs concerning the efficacy and safety of ECT (The UK ECT Review Group 2003). On a worldwide scale, the number of patients receiving unmodified ECT is large, nearly 20,000 of patients in India (Chanpattana et al 2005b), over 6000 in Thailand (Chanpattana and Kramer 2004), and overall in Asia estimated at 11.2 patients treated with unmodified ECT per 100,000 (Chanpattana 2010). …”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, ECT was first administered unmodified in 1950, modified in 1974, and brief-pulse wave first applied in 1992 (Chanpattana 2010). Whereas, in Japan, ECT was first administered unmodified in 1939 and modified 1958 (Chanpattana et al 2005a), but even so the practice of unmodified ECT in Japan in the 1990s is still profuse (Motohashi et al 2004; Chanpattana et al 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…The history and development of psychology and counseling in Thailand can be traced to early efforts to build a secure, modern, and democratic society by offering formal and Western‐oriented education and providing mental health care for Thais during the 42‐year reign (1868–1910) of King Chulalongkorn (Rama V; Bhanthumnavin, 1987; Chanpattana, 2010).…”
Section: Historical Backgroundmentioning
confidence: 99%